What's in a Grade? Teacher Candidates' Experiences of Grading in Higher Education: A Phenomenographic Study - Cormac McGrath; Ylva Ståhle; Lena Geijer (MDPI AG, 2021)
This study explores teacher candidates' experiences of grading in higher education. A phenomenographic approach was adopted and four qualitatively different categories were identified. Grading was experienced as: self-identification, motivation, personal interpretation and academic enculturation. The results indicate that teacher candidates accept existing grading systems but have difficulty interpreting and explaining them, illustrating areas of importance in teacher education and argues that if teacher candidates do not perceive genuine differences in the performance of assessing by grade descriptors, there is a risk that they may develop an insufficient understanding of grading practices.